Behavioral responsive regulation: Bringing together responsive regulation and behavioral public policy. (11th August 2021) - Barak‐Corren, Netta; Kariv‐Teitelbaum, Yael
Abstract: The ambition to improve regulators' responsiveness to regulatees has been the driving force of two of the most influential theories in regulation in the past decades: responsive regulation (RR) and behavioral public policy (BPP). Yet despite their substantial impact and shared ambitions, RR and BPP have rarely intersected. In this paper, we explore the intellectual evolution of RR and BPP and compare their differences in assumptions, methodology, and prescriptions. We argue that these differences can be leveraged to promote both theories and generate a synthesis – behavioral responsive regulation (BRR) – that surpasses its progenitors in helping to understand and improve regulation. We offer an expanded regulatory pyramid for BRR and illustrate the advantages of our approach in many contexts and particularly through the example of taxation. Finally, we argue that BRR promotes the effectiveness, efficiency, and legitimacy of regulation and is superior in these dimensions to both RR and BPP.